Is there an overlooked "window of opportunity" in MS exercise therapy? Perspectives for early MS rehabilitation. (June 2018) - Riemenschneider, Morten; Hvid, Lars G; Stenager, Egon; Dalgas, Ulrik
While early medical treatment has proven effective in MS, early-phase MS rehabilitation has not gained much attention in MS research and clinical practice. Exercise therapy is one of the most promising treatment strategies in MS rehabilitation. Here, we provide a topical review investigating when exercise therapy is initiated in existing MS studies, showing that exercise is initiated at a rather late disease stage, where it predominantly serves as a symptomatic treatment. Recent findings in MS suggest that exercise may have neuroprotective and disease-modifying effects. Such findings along with the findings from medical trials that an early-stage "window of opportunity" exists leads to the proposal that early exercise therapy should be an increased focus in research and clinical practice for persons with MS. A further perspective relates to other rehabilitation interventions that are also initiated at a later disease stage, as these may also take advantage of an early-phase approach.